2018
DOI: 10.1002/wat2.1334
|View full text |Cite
|
Sign up to set email alerts
|

Defining “water resilience”: Debates, concepts, approaches, and gaps

Abstract: Resilience is increasingly applied the context of water systems, and water governance more broadly, in response to climate change impacts, hydrologic variability and uncertainty associated with various dimensions of global environmental change. However, the meanings, applications and implications of resilience as it relates to water governance are still poorly understood. Drawing on a systematic scoping review of the peer‐reviewed academic literature, this paper addresses the questions: how is resilience frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 100 publications
2
66
0
Order By: Relevance
“…Similarly, robotic technologies Water 2019, 11, 1959 4 of 17 and AI, which have been making great strides in the manufacturing and consumer industries, are starting to find their way to water management, e.g., underground asset inspection [22]. Lastly, the authors argue that with these data, tools and models at hand, the sector is now developing more sophisticated ways of stress-testing new and existing infrastructure, developing new methodological approaches around resilience [23]. In the remaining part of this section, a brief overview of some key literature on the subjects highlighted above is provided and an outline of their current state of art is discussed.…”
Section: From Theory To Practicementioning
confidence: 99%
“…Similarly, robotic technologies Water 2019, 11, 1959 4 of 17 and AI, which have been making great strides in the manufacturing and consumer industries, are starting to find their way to water management, e.g., underground asset inspection [22]. Lastly, the authors argue that with these data, tools and models at hand, the sector is now developing more sophisticated ways of stress-testing new and existing infrastructure, developing new methodological approaches around resilience [23]. In the remaining part of this section, a brief overview of some key literature on the subjects highlighted above is provided and an outline of their current state of art is discussed.…”
Section: From Theory To Practicementioning
confidence: 99%
“…In recent years, the term 'resilience' has seen a sudden and marked increase in use and application, in both academia, and policy discourse, with the term now in common parlance across many facets of society. In general terms, resilience is understood to be the ability to withstand shocks and stresses, whilst continuing to maintain key functions and or structures [16]. Many researchers agree that the etymological roots of the term stem from the ability of a system to 'bounce back' [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Like many sectors and fields, resilience and its associated properties have seen a marked increase in popularity across fields of global environmental research as a whole [25] as well as more specifically in water management and governance [6,[26][27][28][29], with both resilience and sustainability following similar trajectories in their rise in application and popularity. A study conducted by Rodina [16] found 149 papers related to water resilience published in the first six months of 2017, with zero publications matching the search criteria in 1982. The increase in use and popularity of the term resilience, specifically in relation to environmental resource governance, are attributed to its focus on the ability to manage complexity, emergence and change, which appeals to systems worldwide that are facing ever-evolving, complex threats and challenges [16,30].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations